Mastering Informatica PowerCenter 9 - Malewar, Rahul (Packt, 2017)
"Informatica is a leader in the ETL market and provides lot of job opportunities in the industry. This course will give you basic to intermediate skills in Informatica, and will help you to prepare for the global certification in Informatica. You'll start the course by learning to debug a mapping, which will help you identify any issues in mappings. You'll be introduced to the advanced aspects of the Designer and Workflow Manager screens. Then you'll find out how to create reusable transformations and mapplets. Then, we move on to working with the target load plan and you'll learn to compare objects. The latter part of the course is centered around using the Workflow Manager screen. You'll learn about the various tasks that are present in Informatica along with the scheduling workflow. We'll also take a look at various aspects of the Admin Console, such as the Repository, Domain, Node, Integration Service, and more. Finally, we'll conclude the course with incremental aggregation, configuring file lists, and working with various types of partitions."--Resource description page